LAW ENFORCEMENT AGAINST ONLINE GAMBLING CRIMINAL OFFICERS BASED ON THE THEORY OF JUSTICE - Aungrah, Sandy Kelvin; Rahmat, Diding (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
Online gambling is one of the negative impacts in the form of cybercrimes, which can be considered a cybercrime. Cybercrimes, especially online gambling, must be prevented or eradicated. Law enforcement efforts are needed to prevent and eradicate these crimes so that they are not increasingly rampant. Therefore, further research will be conducted on how online gambling criminal acts are regulated based on Indonesian laws and regulations, and how law enforcement against online gambling criminal actors is based on the theory of justice. The research method used in this research is the normative juridical research method. From the research results, it was found that the regulation of online gambling criminal acts based on Indonesian laws and regulations, conventional gambling in Indonesia has the potential to cause social and financial risks for players and the surrounding community. Basically, online gambling is a prohibited act in Article 27 paragraph (2) of Law 1/2024. referring to gambling provisions in terms of offering or providing opportunities for gambling games, making it a livelihood, offering or providing opportunities to the public to gamble, and participating in companies for that purpose. Then, people who violate the provisions of Article 27 paragraph (2) of Law 1/2024 are potentially sentenced to a maximum of 10 years in prison and/or a maximum fine of Rp10 billion, as regulated in Article 45 paragraph (3) of Law 1/2024. Article on Gambling in the Criminal Code, For information, in addition to being regulated in Law 1/2024, gambling crimes are also regulated in Article 303 and Article 303 bis of the Criminal Code and Article 426 and Article 427 1/2023 concerning the new Criminal Code and law enforcement against online gambling criminal actors based on the theory of justice, law enforcement against online gambling crimes based on the theory of justice will produce effective and fair law enforcement, and pay attention to the balance between strict law enforcement and respect for human dignity. From the research results for improvement, it is hoped that a new law will be made regarding online gambling crimes in the Criminal Code, laws and regulations, government regulations, Minister of Law and Human Rights regulations, and law enforcement against online gambling criminal actors must be firm and fair in the form of criminal sanctions while still paying attention to human rights.